NBA "bubble" uncovers impact of travel on athletic performance - McKeveny, M. (Fusionsport, 2020)
In response to COVID-19, the NBA paused its 2020 season, resuming 5 months later with a "Bubble" in Orlando, Florida. All 22 teams involved in the season restart travelled to and stayed `on campus` in Orlando for the 14 week bubble.